Active Control of Offshore Steel Jacket Platforms - Zhang, Bao-Lin; Han, Qing-Long; Zhang, Xian-Ming; Tang, Gong-You (Springer Nature Singapore : Imprint: Springer, 2019)
Offshore platforms are widely used to explore, drill, produce, store and transport ocean resources, and are usually subjected to environmental loading, which can lead to deck facility failure and platform fatigue failure, inefficient operation and even crew discomfort. In order to ensure the reliability and safety of offshore platforms, it is important to explore effective ways of suppressing the vibration of offshore platforms. This book provides a brief overview of passive, semi-active and active control schemes to deal with vibration of offshore platforms. It then comprehensively and systematically discusses the recent advances in active systems with optimal, sliding model, delayed feedback and network-based control. Intended for readers interested in vibration control and ocean engineering, it is particularly useful for researchers, engineers, and graduate students in the fields of system and control community, vibration control, ocean engineering, as wellas electrical and electronic engineering.